1986
DOI: 10.1002/1097-4679(198605)42:3<417::aid-jclp2270420303>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Thought disorder and schizophrenia: Isolating and timing a mental event

Abstract: This study explored the ability of nonparanoid schizophrenic, paranoid schizophrenic, and mixed psychiatric control (manics and schizoaffectives) patients to perform on two types of conceptual, speeded inference (SI) tasks, which differ in type of abstraction process required. The subjects (N = 30) were grouped into high and low levels of thought dysfunction, as measured by the Whitaker Index of Schizophrenic Thinking (WIST). There were no differences among the three clinical groups on the conceptual, SI tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Most of the studies measured some form of verbal ability, most often vocabulary, which was tested with several standardized instruments: the Vocabulary subtest from various versions of the WAIS, the Shipley-Hartford Institute of Living Scale Vocabulary subtest (Shipley 1939), and the Mill Hill Vocabulary Test (Raven 1982). Of the investigations specifically examining vocabulary test scores (Russell and Page 1976; Hamlin and Folsom 1977; Neufeld 1977; Asarnow and Mann 1978; Cox and Leventhal 1978; Kay 1979; Magaro and Page 1983; Sengel and Lovallo 1983; Sengel et al 1985; Pishkin and Lovallo 1986; Rosse et al 1991), only two (Hamlin and Folsom 1977; Magaro and Page 1983) reported significant differences, with the paranoid subtype having better vocabulary performance in each case.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Most of the studies measured some form of verbal ability, most often vocabulary, which was tested with several standardized instruments: the Vocabulary subtest from various versions of the WAIS, the Shipley-Hartford Institute of Living Scale Vocabulary subtest (Shipley 1939), and the Mill Hill Vocabulary Test (Raven 1982). Of the investigations specifically examining vocabulary test scores (Russell and Page 1976; Hamlin and Folsom 1977; Neufeld 1977; Asarnow and Mann 1978; Cox and Leventhal 1978; Kay 1979; Magaro and Page 1983; Sengel and Lovallo 1983; Sengel et al 1985; Pishkin and Lovallo 1986; Rosse et al 1991), only two (Hamlin and Folsom 1977; Magaro and Page 1983) reported significant differences, with the paranoid subtype having better vocabulary performance in each case.…”
Section: Resultsmentioning
confidence: 98%
“…However, the CPZ equivalents may not be useful for some medications (e.g., risperidone and haloperidol decanoate). Most of the studies that specifically examined the effects of medication on dependent variables found no significant medication effects (e.g., Pishkin and Lovallo 1986).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations